Ewing’s Sarcoma of Kidney- a Rare Case - Thapa, Bikash Bukram; Thapa, Narayan; Bhandari, Bharat Bahadur; Hamal, Bhairab Kumar (Medical Journal of Shree Birendra Hospital, 2016)
Ewing’s sarcoma of kidney is rare and aggressive tumor of young adult with diagnostic challenges. Clinical presentations and imaging are non specific. The diagnosis depends on histopathology and immunohistochemistry and treatment encompass multimodality approach. We present here a case of Ewing’s sarcoma kidney of a young adult managed in our institution.